2015
DOI: 10.4315/0362-028x.jfp-14-471
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Ochratoxin A Contamination and Detection of Ochratoxigenic Aspergillus Species in Retail Samples of Dried Fruits and Nuts

Abstract: Ochratoxin A (OTA) is a mycotoxin produced by several species of Aspergillus and Penicillium and is a potential contaminant of a wide variety of food products. To determine the incidence of OTA contamination in dried fruits and tree nuts, retail packaged and bulk raisins, dates, figs, prunes, almonds, pistachios, and walnuts were collected from small and large supermarkets in seven areas of the United States between 2012 and 2014. Of the 665 samples analyzed, OTA was detected in 48 raisin samples, 4 fig sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 48 publications
0
23
0
1
Order By: Relevance
“…Palumbo et al (2015) described the OTA methodology and contamination observed in dried fruits and nuts; Lee and Ryu (2015) describe the OTA methodology and contamination observed in breakfast cereals; and Al-Taher et al (2017a,b) describe the OTA methodology and contamination observed in infant cereal, infant formula and milk. For materials and methodology for those foodstuffs, please refer to the cited references.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Palumbo et al (2015) described the OTA methodology and contamination observed in dried fruits and nuts; Lee and Ryu (2015) describe the OTA methodology and contamination observed in breakfast cereals; and Al-Taher et al (2017a,b) describe the OTA methodology and contamination observed in infant cereal, infant formula and milk. For materials and methodology for those foodstuffs, please refer to the cited references.…”
Section: Methodsmentioning
confidence: 99%
“…Samples included organic, traditional and imported products. Further description of the sampling methods and contamination of OTA in the sampled food commodities can be found in previous work conducted by our group (Lee and Ryu 2015; Palumbo et al 2015; Al-Taher et al 2017). Contamination values for wine, coffee, cocoa and pork are being reported for the first time in this risk assessment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples were homogenized by grinding in an electric food grinder, and 25 g of each was subsampled for OTA extraction. OTA was extracted according to the Vicam OchraTest protocol for raisins (Vicam, Milford, MA), as previously described (22). Extracts were analyzed by high-pressure liquid chromatography using an Agilent model 1260 system (Agilent Technologies, Santa Clara, CA) and a Prodigy ODS 3 column (5-lm particle size, 4.6 by 250 mm; Phenomenex, Inc., Torrance, CA), and OTA peaks were quantified relative to an OTA standard curve, as previously described (22).…”
Section: Methodsmentioning
confidence: 99%